The Problem of the Criteria of Scientific Progress in I. Lakatos’ Philosophy - Plėšnys, Albinas (Problemos, 1988)
Verificationism as well as falsificationism tried to formulate the universal criteria of rationality by the way of explicating the logical foundations of science. Historical studies, however, have revealed the fact of the changeability of the criteria. Because of the fact some philosophers have withdrawn their pretensions to create a normative methodology. However, it is possible to find historical invariants in the sequence of the changeable scientific regulations and thus to rehabilitate the normative philosophy of science (the norms of science are viewed here as the principles of the existing decisions). In the article the normative reconstruction of the growth of knowledge proposed by I. Lakatos is being considered.